1-Methyl-2-[(E)-2-(2-thienyl)ethenyl]quinolinium iodide - Ruanwas, Pumsak (International Union of Crystallography, 2008)

(untitled)
In the title compound, C(16)H(14)NS(+)·I(−), the cation has an E configuration about the C=C double bond of the ethylene unit. The dihedral angle between the thiophene ring and the quinolinium ring system is 11.67 (11)°. A weak C—H⋯S intramolecular interaction involving the thiophene ring generates an S(5) ring motif. In the crystal structure, the iodide ion, located between the cations arranged in an antiparallel manner, forms weak C—H⋯I interactions. The crystal structure is further stabilized by a π–π interaction between the thiophene and pyridine rings; the centroid–centroid distance is 3.6818 (13) Å.